Predictive value of early neutrophil-to-lymphocyte ratio and C-reactive protein in pediatric steroid-sensitive nephrotic syndrome - Maimaititusvn, Gulinuer; Jvnaiti, Nilupaer; Kulaixi, Maierhaba; Liu, Fang (Frontiers in Nephrology, 2025)
ObjectiveThis study aims to investigate the predictive value of early neutrophil-to-lymphocyte ratio (NLR) and C-reactive protein (CRP) levels for relapse and adverse prognosis within one year in children diagnosed with steroid-sensitive nephrotic syndrome (SSNS).MethodsThis study included a total of 145 pediatric patients diagnosed with steroid-sensitive nephrotic syndrome (SSNS) between January 2016 and December 2021. We collected early neutrophil-to-lymphocyte ratio (NLR) and C-reactive protein (CRP) levels, along with relevant clinical data, and conducted a one-year follow-up of the patients. Based on the follow-up outcomes, the patients were categorized into two groups: those who experienced a relapse and those who did not. We assessed the diagnostic and predictive value of NLR and CRP for relapse within one year using receiver operating characteristic (ROC) curve analysis and the Cox proportional hazards regression model.ResultsAfter an average follow-up period of one year, 95 patients (65.52%) experienced relapse, while 50 patients (34.48%) did not. Significant differences were noted between the relapse and non-relapse groups regarding neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), C-reactive protein (CRP), 24-hour urinary protein levels, age at onset, and parental education level (P < 0.05). Cox proportional hazards regression analysis identified age at onset, NLR, CRP, and 24-hour urinary protein levels as significant risk factors for relapse in patients with steroid-sensitive nephrotic syndrome (SSNS). Receiver operating characteristic (ROC) curve analysis for the combined prediction of relapse using NLR, CRP, and 24-hour urinary protein levels demonstrated good predictive value, with an area under the curve (AUC) of 0.858 (95% CI: 0.80–0.916, P < 0.001). Kaplan-Meier survival analysis indicated that patients with elevated NLR (≥ 2.90) and CRP (≥ 25.30) exhibited the highest relapse rates and shorter survival times. Further Cox proportional hazards analysis revealed that children in the high NLR and high CRP groups were at an increased risk of relapse, rehospitalization, infection, prolonged cumulative steroid use, renal insufficiency, secondary hypertension, and other adverse outcomes within one year.ConclusionEarly levels of Neutrophil-to-Lymphocyte Ratio (NLR) and C-Reactive Protein (CRP) demonstrate significant predictive value for relapse and adverse prognosis within one year in children with Steroid-Sensitive Nephrotic Syndrome (SSNS). These markers can serve as effective tools for auxiliary clinical assessment.